2020
DOI: 10.1080/22221751.2019.1710435
|View full text |Cite
|
Sign up to set email alerts
|

Increased inflammation with crude E. coli LPS protects against acute leptospirosis in hamsters

Abstract: Leptospirosis is a worldwide zoonotic disease that causes acute kidney injury, liver disease, bleeding disorders, and even death. Treatment of the disease is largely dependent on the use of antibiotics, but recent studies on pathogenesis of leptospirosis have shown that immunomodulation may also be an effective treatment for this disease. Since the delay in inflammation correlates with higher pathogenicity of leptospira, we studied the effect of inducing inflammation on leptospirosis by using TLR4 activator LP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…Along the same line, LPS from E. coli, a very well-characterized TLR4 agonist, when administered 24 h before infection followed by 3 days postinfection, produced 100% survival. Untreated hamsters died in the first days after infection, while the administration of a single dose of LPS 24 h post-infection generated about 50% survival, reinforcing the notion that an early inflammatory response is important to control leptospirosis (86). An interesting observation in those studies was that while Pam3CSK4 showed a tendency to reduce the bacterial burden in organs; this was not observed after using LPS.…”
Section: Use Of Toll-like and Nod-like Receptor Agonists As A Novel Vaccine Strategymentioning
confidence: 79%
“…Along the same line, LPS from E. coli, a very well-characterized TLR4 agonist, when administered 24 h before infection followed by 3 days postinfection, produced 100% survival. Untreated hamsters died in the first days after infection, while the administration of a single dose of LPS 24 h post-infection generated about 50% survival, reinforcing the notion that an early inflammatory response is important to control leptospirosis (86). An interesting observation in those studies was that while Pam3CSK4 showed a tendency to reduce the bacterial burden in organs; this was not observed after using LPS.…”
Section: Use Of Toll-like and Nod-like Receptor Agonists As A Novel Vaccine Strategymentioning
confidence: 79%
“…Then, it was centrifuged at 12000 rpm and 4 °C for 5 min. The pellets were extracted using the TIANamp Bacteria DNA kit (Tiangen, China) according to the manufacturer's instructions [26] . The concentration of DNA was measured by spectrometry.…”
Section: Bacterial Load and Qpcr Assaymentioning
confidence: 99%
“…Hence, despite being responsible for cellular activation and inflammation in vitro , TLR2 triggering is not essential to mouse defense. Indeed, in contrast with TLR4 knockout (KO) mice, TLR2KO mice do not die from experimental leptospirosis ( 116 , 126 ). However, activation of TLR2 in addition to TLR4 contributes to host protection in mice by triggering cytokine secretion and leptospire-specific IgG, NO, and IFNγ secretion ( 116 ).…”
Section: Part Ii—leptospires: Stealthy Pathogens That Escape Several mentioning
confidence: 99%
“… Enhancement of the immune system to better control leptospires. (A) Coinjection at the time of leptospiral infection of PRR agonists such as Pam3CSK (a TLR2 agonist) ( 138 ), β-glucan (a Dectin-1 agonist that potentially synergizes with TLR2) ( 139 ), or crude Escherichia coli LPS (a TLR2/TLR4 agonist) ( 126 ) leads to enhancement of hamster immune responses along with improved survival or delayed lethality and reductions in the number of survivors in tissue lesions, bacterial loads, and inflammation. (B) Recently, innate immune memory or trained immunity has been explored as a therapeutic strategy against leptospires.…”
Section: Part Iii—tlr/nlr Agonists Boost Phagocytic Responses Againstmentioning
confidence: 99%
See 1 more Smart Citation